Using a membrane-penetrating-peptide to anchor ligands in the liposome membrane facilitates targeted drug delivery - Fan, Xiaobo; Xu, Hongbo; Song, Junlong; Jin, Yongcan; Wink, Michael; Wu, Guoqiu (Bioconjugate chemistry, 2020)
Antimicrobial peptides (AMPs) are typical cell penetrating peptides (CPPs) that intercalate into biomembranes and exhibit broad activities. We designed a triple fusion protein consisting of an AMP, Ib-AMP4 at the N-terminus, a fluorescent GFP probe in the center, and the tumor-targeting peptide P1c at the other terminus. After purification from E. coli, the interaction between the Ib-AMP4-GFP-P1c fusion protein (IGP) and the lipid membrane was characterized. Experiments using isothermal titration calorimetry (ITC) and quartz crystal microbalance with dissipation (QCM-D) demonstrated that IGP proteins spontaneously bound the lipid bilayer with a maximal molar ratio of 1:52 (protein:lipid). Furthermore, transmission electron microscopy (TEM) confirmed that the IGP protein was present in the liposome membrane. After decoration with IGP proteins, the DOPC:DOPG liposomes were applied to cancer cells. Microscopy and flow cytometry reveal that the decorated liposomes selectively bound integrin αvβ3-positive A549 cells. In addition, compared with the common chemical conjugation method, the reported method seemed to be superior in certain aspects, such as simple sample preparation and cost-effectiveness. Next, the IGP protein was applied to decorate red blood cell (RBC) liposomes for targeted delivery in both in vitro and in vivo applications. The IGP-decorated RBC liposomes preferentially targeted integrin αvβ3 expressing A549 cancer cells. The in vivo imaging showed that IGP-decorated RBC liposomes were concentrated in tumor tissue and were primarily metabolized by the liver and kidney.